2005
DOI: 10.1021/es0504892
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Factors on Efficacy of Upper-Room Air Ultraviolet Germicidal Irradiation for Inactivating Airborne Mycobacteria

Abstract: This study evaluated the efficacy of an upper-room air ultraviolet germicidal irradiation (UVGI) system for inactivating airborne bacteria, which irradiates the upper part of a room while minimizing radiation exposure to persons in the lower part of the room. A full-scale test room (87 m3), fitted with a UVGI system consisting of 9 louvered wall and ceiling fixtures (504 W all lamps operating) was operated at 24 and 34 degrees C, between 25 and 90% relative humidity, and at three ventilation rates. Mycobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
90
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 27 publications
8
90
0
2
Order By: Relevance
“…Since then, several additional studies have shown reduction of bacterial spores and vegetative cells due to upper room air UV irradiation (Miller and Macher 2000;Ko et al 2002;Xu et al 2003Xu et al , 2005Rutala et al 2010). In addition to hospital rooms, installation of UV lights in office ventilation systems has also been shown to reduce the airborne bacterial load.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several additional studies have shown reduction of bacterial spores and vegetative cells due to upper room air UV irradiation (Miller and Macher 2000;Ko et al 2002;Xu et al 2003Xu et al , 2005Rutala et al 2010). In addition to hospital rooms, installation of UV lights in office ventilation systems has also been shown to reduce the airborne bacterial load.…”
Section: Introductionmentioning
confidence: 99%
“…Upper-room 254-nm germicidal UV (UVC) light, often referred to as UV germicidal irradiation, has been shown to be an efficient and economical means of air disinfection for tuberculosis and other airborne infections (1,11,18,22,23). If organisms circulate from the lower room to the upper room (i.e., if there is adequate mixing of room air) and receive an adequate dose of UVC, upper-room UVC can potentially lower the concentration of infective organisms in the lower part of the room and thereby control the spread of airborne infections among room occupants without exposing the occupants to a significant amount of UV radiation (1,4,23).…”
mentioning
confidence: 99%
“…The expansion of care, entailing congregation in overcrowded settings of highly susceptible persons with those most likely to have TB, accentuates the need for effective prevention of TB transmission. Upper-room UV light is an effective and relatively low-cost environmental control measure already recommended as an adjunctive measure by guidelines but little used owing to the lack of studies in clinical settings until now [18].…”
Section: Resultsmentioning
confidence: 99%